2016
DOI: 10.1183/16000617.0080-2015
|View full text |Cite
|
Sign up to set email alerts
|

Short-course treatment for multidrug-resistant tuberculosis: the STREAM trials

Abstract: Multidrug-resistant (MDR) tuberculosis (TB) is a threat to global TB control, as suboptimal and poorly tolerated treatment options have resulted in largely unfavourable outcomes for these patients. The last of six cohort studies conducted in Bangladesh which assessed a new shorter regimen using currently available TB drugs showed promising results and offered the possibility of a more acceptable and more effective regimen than the one recommended by the World Health Organization (WHO). The aims of stage 1 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 12 publications
0
90
0
3
Order By: Relevance
“…Clinical trials are underway with regimens that exclude aminoglycosides, but depend upon the activity of oral drugs including fluoroquinolones [7]. Yet in prior studies of MDR-TB in Bangladesh, we found high proportions of patients with M. tuberculosis isolates with resistance or borderline susceptibility to fluoroquinolones, while susceptibility to an aminoglycoside was retained [8].…”
Section: To the Editormentioning
confidence: 99%
“…Clinical trials are underway with regimens that exclude aminoglycosides, but depend upon the activity of oral drugs including fluoroquinolones [7]. Yet in prior studies of MDR-TB in Bangladesh, we found high proportions of patients with M. tuberculosis isolates with resistance or borderline susceptibility to fluoroquinolones, while susceptibility to an aminoglycoside was retained [8].…”
Section: To the Editormentioning
confidence: 99%
“…Ideally, using molecular assays provide rapid results. Rapid diagnosis of (pre-)XDR is becoming important especially now that the 9-month 'Bangladesh' regimen is showing promise [99,100] and results from a clinical trial are expected soon [101]. WHO recently endorsed this short-course regimen for MDR-TB [19].…”
Section: Potential Role Of Host-derived Biomarkers In Treatment Guidancementioning
confidence: 99%
“…It is not recommended for pregnant women and patients with extrapulmonary TB 1. This recommendation is based on observational studies2–4 as well as on the STREAM (Evaluation of a Standardised Treatment Regimen of Anti-tuberculosis Drugs for Patients with Multidrug-resistant Tuberculosis) trial performed in Asia and Africa 5…”
mentioning
confidence: 99%